Bureau d'intervention et de prévention - École nationale de cirque - Montréal (École nationale de cirque, 2023)
Le BIP de l'ÉNC vise à prévenir et intervenir en cas de discrimination, de harcèlement et de violence au sein de son établissement.
Keywords: Sophie-Anne

SPEAK OUT: together for a safer circus - Fédération européenne des écoles de cirque (FEDEC); JUMP (2023)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Femmes de spectacle au XIXe siècle - Ponzetto, Valentina; Fix, Florence (2022)
Quelle est la place des femmes dans l’industrie du spectacle du XIXe siècle au-delà des métiers de performance très exposés qu’exercent les actrices, ...
Keywords: Sophie-Anne

We protect animals well": A structural approach to abusive conduct within circus schools - Matthis, Rosa (Linköping University, 2021)
This master thesis investigates abusive conduct in circus schools. Focus is put on the management level in order to achieve and provide knowledge of measures and attitudes related to prevention. Th ...
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics